JURIDICAL STUDY CONCERNING PARTICIPATION IN ADULTERY REVIEWED FROM ISLAMIC LAW AND THE CREDIT - Rahmat Ibrahim Hasibuan; M. Anshari Lubis; Roni Risky Nasution; Maurizio Zanardi (PT. Radja Intercontinental Publishing, 2023)
The problem raised as the focus of the research is what is the position of the perpetrator of adultery according to the Criminal Code and Islamic law and how to participate in adultery according to the Criminal Code and Islamic law. The type of research used by the author in this research is library research, also known as Library Research, namely by searching for data or information through searching the literature available in the library. As well as using a comparative approach method (Comparative Approach) because the author examines participation in adultery according to the Criminal Code and Islamic law to show a comparison of participation in adultery according to Islamic law with positive law. The data source used in this research is a secondary data source, which contains legal materials. The primary legal materials used by researchers are the Criminal Code, the Qur'an and Hadith. The secondary legal materials used by researchers are scientific books, books of fiqh, texts from the mass media, journals and/or other references that are relevant to the problem being studied. The tertiary legal materials used by researchers are encyclopedias, legal dictionaries and Indonesian dictionaries. The conclusions that can be drawn from this thesis are, first, the position of the perpetrator of adultery according to the Criminal Code and Islamic law is that a person can be considered a perpetrator of adultery when that person carries out sexual activities, namely the entry of a man's genitals into a woman's genitals, the difference between Indonesian positive law and Islamic law. that is, it lies with the perpetrator. In Indonesian positive law the perpetrator must be a person who is bound by marriage and there must be a complaint from his legal wife/husband, however in Islamic law the perpetrator does not have to be bound by marriage and there does not have to be a complaint. Second, participating in adultery according to the Criminal Code and Islamic law means that the Criminal Code views participating in adultery as the activity of a person who, together with the perpetrator of adultery, carries out some of the elements of the criminal act of adultery so as to achieve the crime of adultery, in the Criminal Code assisting, encouraging and ordering the commission of a criminal act is a separate sub-chapter and is not included in participation, however in Islamic law participation covers everything related to the expansion of perpetrators of criminal acts, so participation in Islamic law includes assistance, encouragement and ordered to commit criminal acts.